Personal Bankruptcy in Malaysia and Singapore: An Empirical Analysis (Journal of Economics and Sustainability, 2022)
The main objective of this study is to examine the dynamic relationship between personal bankruptcy and Gross Domestic Product (GDP), Consumer Price Index (CPI), Interest Rate (IR), Household Debt (HD), and Unemployment (UE) in Malaysia and Singapore. This study covered time series annual data from 2000 to 2019. ARDL and Variance decompositions were used to test the model. The findings for Malaysia show that CPI and IR are negatively and significantly related to personal bankruptcy in the long run, while HD has a positive relationship. In contrast, CPI shows a positive impact while IR negatively impacts personal bankruptcy in the short run. However, for Singapore, CPI and HD have a negative and positive significant impact on personal bankruptcy, respectively, in the long run. On the other hand, CPI shows a positive and significant relationship with personal bankruptcy in the short run. HD has a positive and significant impact on bankruptcy for both countries. On the other hand, CPI and IR show different impacts on personal bankruptcy in Malaysia and Singapore. The difference in the impact of these macroeconomic variables on bankruptcy in Malaysia and Singapore implies that policies and regulatory reforms to managing personal bankruptcy should be country-specific against the backdrop of different economic environments.